PENGARUH KETERLAMBATAN PROSES PENGADAAN TANAH TERHADAP PENCAPAIAN WAKTU PROYEK - M. Arif Nugraha; Cut Zukhrina Oktaviani; Alfa Taras Bulba (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2022)
Land acquisition for the Jambo Aye Kanan Irrigation Network of ± 35 kilometers was started in 2010 and is currently around 28 kilometers or ± 70% of the total land acquisition. The Lhok Guci irrigation network of ± 90 kilometers was started in 2007 and is currently around 45 kilometers or ± 50% of the total land acquisition. It can be concluded that if the land acquisition has not been completed, the project work will be carried out as an addendum. In general, a contract addendum is an addition to the main agreement. Additions or changes that are attached cannot be separated from the main agreement, must remain in accordance with the unity of the agreement. Addendum to this contract can be made even though the term of the agreement has not ended, as long as all parties agree. Based on the description above, the problems identified are what factors are causing delays in land acquisition and the impact of the land acquisition process on the project time. This study aims to identify the effect of the land acquisition process on the achievement of project time performance. The results of this study are expected to be one of the references and information to overcome the problems that have resulted in delays in the completion of the Jambo Aye Kanan irrigation network project and the Lhok Guci irrigation network. The method used in this research is correlation analysis. The results of the correlation analysis using the SPSS application that have a relationship with the land acquisition process on the achievement of time performance are funds/funding, coordination and price. The result of the highest correlation analysis of the factors that influence land acquisition on time performance is the price variable. The correlation of the variables that affect land acquisition with laws and regulations on the time performance variable has a high correlation.